Successful professional reviews for civil engineers - Steels, H. Macdonald (London : ICE Publishing, 2011)
Provides a comprehensive guide to the constituent parts of the ICE Professional Review process, ideal for those engineers nearing the completion of thier initial professional development. Working logically through the review process, the chapters ensure that the review candidate is provided with an in-depth understanding of the criteria by which he or she will be assessed and how the demonstrate these in the final professional reveiw. It also details how any candidate, from any background, might consider demonstrating the attributes which the reviewers are seeking. It offers many siggestions, examples and anecdotes to assist and guide each individual as they set about the achieving success. -- BACK COVER
Includes bibliographical references and index.
Keywords: Civil engineers -- Rating of -- United Kingdom; Civil engineers -- Certification -- United Kingdom